Mapping the Evolution and Practical Significance of Implied Terms in Contracts: Insights from the United Kingdom and Nigerian Legal Frameworks - Joseph Agburuwhuo Nwobike (Studies in Law and Justice, 2025)
Since The Moorcock case in 1889, the boat of implied terms has encountered storms and instability from scholarly debates. The key contentious issues orbit around the role of reasonableness, necessity, contract interpretation, and the continued relevance of the traditional tests. Historically, courts have used two main tests to imply terms into contracts: Lord Bowen’s Business Efficacy Test and Lord Mackinnon’s Officious Bystander Test. However, in Belize Telecom Ltd (2009), Lord Hoffmann opined that implying terms in contract is simply part of interpreting the contract as a whole, rather than applying the traditional tests: in response to this approach, a significant weight of judicial authority supports the view that Belize should not be perceived as a relaxation of the traditional tests towards implication of terms. While debates have continued on whether implied terms of fact should be a distinct process or simply part of contract interpretation, the UK Supreme Court in Barton v Morris (2023) held that if a term is sufficiently express, the doctrine of unjust enrichment and quantum meruit cannot be used to imply a term that possibly contradicts the express term––this is somewhat different from the position of law in Nigeria. This article is an illuminating synthesis of these differences: it charts a stable and harmonized course that smoothens out the rough patches which accrued over the years via intense legal polemics.